<DATA REPORT>RECORDS OF RADIO AURORA AT SYOWA STATION, ANTARCTICA IN 1993 and 1994 - IWASAKI, Kyoji; YAMAGUCHI, Takashi; IGARASHI, Kiyoshi (National Institute of Polar Research, 1997)
P(論文) departmental bulletin paper